Implementasi Kebijakan Pariwisata Di Desa Kalipucang Kecamatan Tutur Kabupaten Pasuruan - Abror, M. Daimul; Jannah, Roudotul (Prodi Sosiologi Agama, 2021)
Kalipucang Village as one of the tourist village areas has tremendous potential in tourism development. However, the socio-economic conditions of the community tend to be relatively simple, so it is necessary to carry out an in-depth analysis related to the Implementation of Tourism Policy in Kalipucang Village, Tutur District, Pasuruan Regency. The purpose of this study is to describe, analyze, and interpret the form of Tourism Policy Implementation in Kalipucang Village by referring to George and Edward III's implementation process model theory. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, with the Village Government, Pokdarwis and local communities as well as documentation. The results showed that the implementation of the tourism policy in Kalipucang Village had been implemented well. communication made by Policy Actors (Village Government) with the community is quite good with the openness of the problems faced. Natural resources are so abundant that the people of Kalipucang Village are enthusiastic in developing the Tourism Village so that it is more famous and visited by many domestic and foreign tourists. The problem faced by the people of Kalipucang Village is that the performance of each field, especially the tourism sector, is not optimal due to limited capital, inadequate tourism supporting facilities and infrastructure, and tourism destinations that are not well organized. Existing supporting factors include the variety of available tourism potential, support from local community leaders and administrators, collaboration between community members and the attitude of kinship and mutual cooperation which is still very strong. Meanwhile, from the practical implications of implementing tourism policies in Kalipucang Village, it shows positive economic and social changes, both from the aspect of tourism destinations, aspects of local icons, aspects of brotherhood and friendship and aspects of community welfare.